2021
DOI: 10.1021/acsomega.1c03245
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Tubes Prefilled with Aligned Fibrin Nanofiber Hydrogel Enhance Facial Nerve Regeneration in Rabbits

Abstract: Facial nerves are fragile and easily injured, for example, by traffic accidents or operations. Facial nerve injury drastically reduces the quality of life in affected patients, and its treatment presents clinical challenges. A promising therapeutic strategy includes nerve conduits with appropriate fillers capable of guiding nerve regeneration. In this study, a three-dimensional hierarchically aligned fibrin nanofiber hydrogel (AFG) assembled via electrospinning and molecular self-assembly was first used to mim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(68 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, tensile tests of chitosan tubes were carried out, and the representative diagrams are shown in Figure 6 E. The stress of four samples was between 7 and 9 MPa, which indicated that the stress of chitosan tubes was relatively stable and the manufacturing method of chitosan tubes was repeatable. The chitosan tube’s mechanical properties analyzed from the tensile test are shown in Figure 6 F. The elastic modulus was 180 ± 40.3 MPa, the tensile strength was 8.6 ± 1.4 MPa, and the breaking elongation was 8.2 ± 1.8%, which was consistent with our previous experimental results 43 and meets the mechanical requirements of nerve conduits. 47 , 48 …”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, tensile tests of chitosan tubes were carried out, and the representative diagrams are shown in Figure 6 E. The stress of four samples was between 7 and 9 MPa, which indicated that the stress of chitosan tubes was relatively stable and the manufacturing method of chitosan tubes was repeatable. The chitosan tube’s mechanical properties analyzed from the tensile test are shown in Figure 6 F. The elastic modulus was 180 ± 40.3 MPa, the tensile strength was 8.6 ± 1.4 MPa, and the breaking elongation was 8.2 ± 1.8%, which was consistent with our previous experimental results 43 and meets the mechanical requirements of nerve conduits. 47 , 48 …”
Section: Resultssupporting
confidence: 88%
“…Three observers evaluated the whisker movements separately every three weeks according to grading standards: 0 means no apparent movement; 1 means almost imperceptible movement; 2 means fewer significant autonomous movements; 3 means significant but an asymmetric autonomous movement; and 4 means symmetric autonomous movement. , …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[197] Inspired by this finding, Wang's team employed a hierarchically aligned fibrin nanofiber hydrogel (AFG) inserted within chitosan tubes as a nerve graft. [62,190] The AFG can mimic the native fibrin cable as well as the oriented and low-elastic features of the nerve ECM, providing an instructive microenvironment to accelerate neurite regrowth. They further functionalized AFG with self-assembling peptide to carry out synergistic topographical and biochemical cues for peripheral nerve regeneration.…”
Section: Peripheral Nervementioning
confidence: 99%